Academic Leadership During a Pandemic: Department Heads Leading With a Focus on Equity - Kruse, Sharon D.; Hackmann, Donald G.; Lindle, Jane Clark (Frontiers in Education, 2020)
The COVID-19 pandemic has created an unprecedented crisis with momentous challenges for higher education institutions. Academic leaders have been charged with restructuring their systems, ensuring instructional quality while operating with significantly diminished resources. For department heads of units with leadership preparation programs, the complexity of this crisis is layered upon fundamental scholarship about leadership, which reports the effectiveness of leadership as a collective incorporating the shared and diverse talents of faculty, students, and program stakeholders. This work of educational leadership rests on a public and democratic ethic promoting social justice and equity as the practices and outcomes for schooling at any level. In this paper, three department heads of educational leadership units in major research universities use dialogic inquiry to reflect on our responses to complex demands brought forth by the pandemic. We share insights into our decision making, as we have led with a focus on equity. We address dilemmas and conflicts that we have addressed as departmental leaders during this critical period of institutional challenges, changing institutional policies and practices, and declining resources, as we have worked to ensure equitable access and distribution of resources for students, faculty, and staff. We conclude with implications for department heads who strive to maintain a focus on equity during times of sweeping organizational change.